Creation of agricultural land market in Ukraine: current state of development; Entwicklung des Bodenmarktes in der Ukraine - Vladimir Melnychuk; Sergiy Parkhomenko; Alexej Lissitsa (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2005)
Land reform started in Ukraine 14 years ago became one of the most important issues in transformation of large state agricultural enterprises into market oriented agricultural enterprises. Significant changes in land use and land ownership has happened as a result of land reform implementation in Ukraine. Namely, state monopoly on land was eliminated, agricultural land was privatized, citizens of Ukraine received land plots in possession, first land transactions have happened at agricultural land market etc. Actual data regarding Ukrainian land relations reformation is systematized in this Discussion paper with especial focus on establishing the prerequisites of further formation and perspective development of the agricultural land market in Ukraine. Additionally, a current situation is described at the Ukrainian agricultural land market and its legislative regulations. – – Die vor 14 Jahren in der Ukraine begonnene Bodenreform stellt eine wichtige Maßnahme der Transformation der ehemaligen staatlichen Agrarunternehmen in marktorientierte Unternehmen dar. Im Ergebnis der Bodenreform haben wichtige Veränderungen bezüglich der Bodennutzung und der Bodeneigentumsverhältnisse stattgefunden. Das staatliche Monopol an Boden wurde beseitigt und der Boden privatisiert. Die ukrainische Bürger erhielten Grundstücke als Eigentum übertragen, und erste Bodentransaktionen haben stattgefunden. Dieses Discussion Paper systematisiert die aktuelle Lage auf dem ukrainischen Bodenmarkt und formuliert weitere Voraussetzungen zur Herausbildung eines voll funktionsfähigen landwirtschaftlichen Bodenmarktes in der Ukraine. Die aktuellen Gesetze werden erläutert.
urn:nbn:de:gbv:3:2-210
Keywords: O13; O17; P26; P32; P48; Q15; Q18; 330; Land market reform; transition; Ukraine; Bodenmarktreform; Transformationsprozess; Ukraine